Curriculum : district stories of a path to improved achievement - Squires, David A. (Education in a competitive and globalizing world series., 2014)
A curriculum is not known to improve academic achievements. This book offers case studies of three Connecticut districts of high, medium and low socio-economic status, three districts from a national sample that won the prestigious Booker prize mainly representing low SES districts, and 10 districts that have implemented a Balanced Curriculum with a sample of various SES districts from high to low. All of them have used their curriculum as the vehicle toward improved achievements. The districts studied have four common themes, represented by the acronym ""ASIA"", for Alignment, Structure and S.